Patronyms and toponyms in Indonesian coral taxonomy, with notes on selected sponge taxa - OKTIYAS MUZAKY LUTHFI; DEWA GEDE RAKA WIADNYA; M. AZUREA BAHRI LUTHFI; ANDIK ISDIANTO; ADE YAMINDAGO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Luthfi OM, Wiadnya DGR, Luthfi MAB, Isdianto A, Yamindago A. 2026. Patronyms and toponyms in Indonesian coral taxonomy, with notes on selected sponge taxa. Biodiversitas 27 (4): d270444. https://doi.org/10.13057/biodiv/d270444. Indonesia is located at the center of the Coral Triangle and has contributed substantially to the discovery and naming of reef-associated taxa. This study aimed to document and analyze patronyms, toponyms, and descriptive epithets in the scientific names of selected scleractinian corals and demosponges associated with Indonesian waters. A focused nomenclatural synthesis was conducted using primary taxonomic literature and biodiversity databases, including WoRMS, GBIF, ZooBank, and the Biodiversity Heritage Library. Twenty-four taxa were analyzed, comprising 16 Acroporidae, five other scleractinian corals, and three Demospongiae. Toponyms were the most frequent epithet type, representing 10 taxa (41.7%), followed by patronyms with eight taxa (33.3%) and descriptive epithets with six taxa (25.0%). Patronyms occurred mainly in Acroporidae, whereas toponyms were more common among other scleractinian corals and demosponges. Several names were associated with Indonesian localities such as Halmahera, Derawan, Bali, Cenderawasih Bay, Bangka, and Maluku, while patronyms recorded the contributions of scientists, collectors, and collaborators involved in Indonesian marine biodiversity studies. These findings show that species names are not only taxonomic labels but also compact records of biogeographic origin, scientific contribution, and taxonomic history. This study highlights Indonesia’s importance as a source of type material and as a major setting in coral and sponge taxonomy.